The role of perceived teacher, peer, and parental support in school belonging among vocational high school students - Rangga Satria Adinata; Wilis Srisayekti; Ratna Jatnika (International Journal of Adolescence and Youth)
This study investigates the role of perceived support from teachers, peers, and parents in fostering school belonging among vocational high school students. A total of 567 students participated in this research. Data were analysed using Structural Equation Modeling – Partial Least Squares (SEM-PLS). The results indicate that perceived teacher emotional support, perceived teacher instrumental support, and perceived parental emotional support significantly predict students’ sense of school belonging. Among these, only perceived teacher emotional support demonstrated a substantive impact, albeit with a small effect size. These findings differ from those of prior studies, suggesting the need for further research that explores how variations in the conceptualization of school belonging and sample characteristics may influence the results.